2016
DOI: 10.1002/ase.1598
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound in graduate anatomy education: Current state of integration in the United States and faculty perceptions

Abstract: Ultrasound (US) is increasingly taught in medical schools, where it has been shown to be a valuable adjunct to anatomy training. To determine the extent of US training in nonmedical anatomy programs, and evaluate anatomists' perceptions on the role of US in anatomy education, an online survey was distributed to faculty in anatomy Master's and Doctoral programs. Survey results sampled 71% of anatomy graduate degree programs nationally. Of the faculty surveyed, 65% report little to no experience with US. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 61 publications
1
50
0
1
Order By: Relevance
“…In recent years, ultrasound has emerged as a popular tool in anatomy teaching to demonstrate dynamic anatomy and to image physiological processes in real time. Ultrasound is valuable for both students and faculty for anatomy teaching and learning and also helps to retain the anatomy knowledge (Pawlina and Drake, ; Royer, ). Virtual 3D‐representation of the body is also used extensively in anatomy education, either using images from real cadavers or from illustrations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultrasound has emerged as a popular tool in anatomy teaching to demonstrate dynamic anatomy and to image physiological processes in real time. Ultrasound is valuable for both students and faculty for anatomy teaching and learning and also helps to retain the anatomy knowledge (Pawlina and Drake, ; Royer, ). Virtual 3D‐representation of the body is also used extensively in anatomy education, either using images from real cadavers or from illustrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 62% included any form of ultrasound education in their curriculum . Similarly, a survey of more than 60 institutions found that 90% of faculty agreed that ultrasound positively contributed to learning anatomy, yet only 36% of the programs incorporated ultrasound into training …”
mentioning
confidence: 99%
“…9 Similarly, a survey of more than 60 institutions found that 90% of faculty agreed that ultrasound positively contributed to learning anatomy, yet only 36% of the programs incorporated ultrasound into training. 10 A lack of financial support was the most-cited reason that medical schools did not implement an ultrasound program. 9 As a result, schools are more dependent on instructor volunteerism to meet their ultrasound curriculum's personnel needs.…”
mentioning
confidence: 99%
“…For example, healthcare has become increasingly reliant upon medical imaging, and as such ultrasound has joined plain film radiography and cross‐sectional imaging (i.e., computed tomography (CT) and magnetic resonance imaging [MRI]) as a mainstay in clinical anatomy training (Hoppmann et al, ; Bahner et al, ; Martinez et al, ; Dinh et al, ). A recent survey by Royer () demonstrated that most anatomists are in favor of utilizing ultrasound in anatomy education, but 65% of survey respondents had minimal, if any, experience with ultrasonography. The continued clinical reliance on imaging modalities underscores the need for anatomists to be competent in teaching various forms of medical imaging, and evidence has shown that anatomists are as capable as clinicians in teaching ultrasound‐based anatomy (Jurjus et al, ).…”
Section: Discussionmentioning
confidence: 99%